Contributing Factors to Customers Loyalty in Gadgets A Study on Apple Brand - Yusof, Rosmelisa; Huei, Lok Yee; Adnan, Nur Aisya; Jefry, Nur Aliah Ilyana; Syuhaimi, Nur Aliana Sofea; Marzuki, Nur Alieza Natasha; Fasya, Nilna Iffa Afifatia; Tsabita, Naura Nuhaa (International Journal of Tourism and Hospitality in Asia Pasific, 2023)
Apple is a well-known technology corporation globally and one of the most valuable brands in 2020. Apple Inc. is a company that designs, develops, and distributes mobile communication and media players, PCs, and portable digital music players. Apple's products include iPhones, iPads, Macs, and iPods.In Malaysia, most university students choose to utilize Apple devices for their studies.This research examines why most students prefer Apple products in their daily lives. This research will also examine customer satisfaction, product quality, and other aspects and attitudes that impact customers' loyalty to Apple products. The data was acquired through monitoring and surveying students at University Sains Malaysia. This paper's analysis approach compares theory to observation and survey data.